Use Of Communication Information Technology On Primary School Teacher Performance In The Developed Areas Of The District North Moyo In 2022/2023 - Atil, Rabiatil; Suparman, Suparman; Junaidi, Junaidi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The role of teachers in the world of education is very important, because the requirement for learning is the presence of a teacher. As teachers who live or are in the current global era, we are required to be creative and master technology so as not to be left behind by the current times. The objectives of this research consist of, 1) the constraints and application of the use of information communication technology on the performance of elementary school teachers in the target area of North Moyo subdistrict. 2) analyzing the influence of the use of information communication technology on the performance of elementary school teachers in the target area of North Moyo subdistrict. The approach used in this research is a mixed method research design. Research methods that combine or combine quantitative methods with qualitative methods. Sampling used total sampling with a total sample of 24 teachers from 3 schools. Meanwhile, data collection uses observation sheets, questionnaires and structured interview guides which are then analyzed. The research results found that the ICT support facilities in the 3 school locations were basically adequate, however, the main obstacle was the internet signal which still could not reach all classrooms. Apart from that, because the school location also caused the internet signal to be less stable. This has an impact on the time efficiency of using ICT. Specific policies related to the integration of ICT in learning. Lack of knowledge and willingness of teachers to learn the use of ICT, lack of intensity of workshops/training related to ICT held by schools. The use of ICT should encourage users to be more creative and innovative so that they are not just satisfied with being consumers of ICT-based information. Performance comes from the definition of performance. Performance has a broader meaning, not just the results of work, but including how the work process takes place. So it is concluded that the use of information and communication technology on teacher performance has not been maximized in implementation in the target area of North Moyo sub-district.